Polyphonic Readers In The Novel "the Bride Of Rain" (arous El Matar) By Buthaina Al-essa. - bourezg, afaf (El Omda in Linguistics and Discourse Analysis, 2025)
The polyphonic narration crystallized as one of the most prominent manifestations of mitigation, in the contemporary Arab novel, in order to practice democracy of expression and reduce narcissistic practice, which was not without any literary work, This is what made the new novelist experiences hear the reader number of conflicting narrative voices, in the space of the narrative structure, from an open site that eliminates the authority and dominance of the ego, which the narrator was exercising, over the reader. On this basis, we will seek to elucidate the technique of polyphony in the novel “The Bride of Rain” and its compatibility with Bakhtin’s textual approach